Prevalence and clinical profile of comorbidity among newly diagnosed pulmonary tuberculosis patients: a multi-center observational study in eastern China - Wang, Wei; Wang, Xiaomeng; Chen, Songhua; Li, Jun; Cheng, Qinglin; Zhang, Yu; Wu, Qian; Liu, Kui; Jiang, Xuli; Chen, Bin (Frontiers in Medicine, 2025)
ObjectiveTo identify the composition of comorbidities among patients with newly diagnosed pulmonary tuberculosis and assess the impact of comorbidities on the clinical characteristics of patients.MethodsThis study was conducted in 13 hospitals across 13 counties in Zhejiang province, China. Patient data collected in this study included demographic characteristics, chest radiography results, etiological results, and comorbidities. Descriptive statistics were conducted to describe the composition of comorbidities of all participants. Univariate and multivariate logistic regression analyzes were performed to identify the effects of comorbidities on the clinical features of the participants.ResultsOf the 8,421 total participants, 27.6% reported cavities in the chest radiography results, 41.9% were Mycobacterium tuberculosis-positive in the etiology test results, and 38.7% (3,258/8,421) had at least one type of comorbidity. The most predominant comorbidity was pleuritis (1,833, 21.8%), followed by diabetes mellitus (763, 9.1%), other extrapulmonary tuberculosis (421, 5%), tracheobronchial tuberculosis (275, 3.3%), and silicosis (160, 1.9%). Participants with diabetes mellitus had the highest rate of chest cavities on X-ray (54.8%), followed by those with silicosis (33.1%). In addition, a higher percentage of the M. tuberculosis-positive etiology (45%) was observed in participants without comorbidities than in participants with comorbidities (37.1%). Compared to patients without comorbidities, patients with diabetes mellitus (adjusted odds ratio [AOR]: 2.88, 95% confidence interval [CI]: 2.42–3.43) were more likely to show cavities in chest X-ray, while patients with pleuritis (AOR: 0.27, 95% CI: 0.23–0.32), other extrapulmonary tuberculosis (AOR: 0.48, 95% CI: 0.36–0.64), and tracheobronchial tuberculosis (AOR: 0.40–0.79) were less likely to show chest cavities in X-ray. In addition, patients with diabetes mellitus (AOR: 2.05, 95% CI: 1.72–2.45), tracheobronchial tuberculosis (AOR: 3.22, 95% CI: 2.4–4.32) were more likely to show Mycobacterium tuberculosis-positive in the etiology, and patients with pleuritis (AOR: 0.25, 95% CI: 0.22–0.29), other extrapulmonary tuberculosis (AOR: 0.61, 95% CI: 0.48–0.76) were less likely to show Mycobacterium tuberculosis-positive in the etiology.ConclusionThe prevalence of comorbidities was high in patients newly diagnosed with pulmonary tuberculosis. Thus, integration of screening and personalized management is needed for the control of tuberculosis and its comorbidities.